A self-tuning robust full-state feedback control design for the magnetic levitation system. (September 2018) - Bidikli, Baris; Bayrak, Alper
Abstract: In this study, a self-tuning robust integral of signum of error (RISE) based controller is designed and used to control a magnetic levitation (maglev) system. In the control design, unlike the classical RISE controller, ' tanh ' function is used instead of ' signum ' function to obtain a more smooth control signal. The gains of the controller are updated according to a time-varying update rule. Convergence of the error under the closed-loop operation is proven via Lyapunov-based stability analysis. The controller is tested on an experimental maglev system and successful results are obtained. Highlights: A nonlinear robust full-state-feedback controller is designed for the control of maglev system. A newly designed self-tuning structure is presented for the adjustment of control gains. Stability analysis of the designed controller is realized via Lyapunov-based arguments. Performance and efficiency of the designed controller are demonstrated via experimental results.